2018
DOI: 10.1038/s41388-018-0490-y
|View full text |Cite
|
Sign up to set email alerts
|

The cell cycle regulatory DREAM complex is disrupted by high expression of oncogenic B-Myb

Abstract: Overexpression of the oncogene MYBL2 (B-Myb) is associated with increased cell proliferation and serves as a marker of poor prognosis in cancer. However, the mechanism by which B-Myb alters the cell cycle is not fully understood. In proliferating cells, B-Myb interacts with the MuvB core complex including LIN9, LIN37, LIN52, RBBP4, and LIN54, forming the MMB (Myb-MuvB) complex, and promotes transcription of genes required for mitosis. Alternatively, the MuvB core interacts with Rb-like protein p130 and E2F4-DP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 45 publications
1
80
1
Order By: Relevance
“…However, it remains unclear whether re-expression of RB in Saos-2 cells would reinforce this weak repression which then would be in agreement with our data. Given that overexpression of B-MYB was shown to disrupt the DREAM complex leading to activation of gene expression dependent on CHR elements (31), the lack of G 2 /M gene repression in RB-negative cells upon doxorubicin treatment may be caused by an increased B-MYB protein expression (Figure 4C). Interestingly, it was also shown that cells expressing high levels of ectopically expressed B-MYB can enter S phase, even when the p53-p21 pathway is activated (62).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it remains unclear whether re-expression of RB in Saos-2 cells would reinforce this weak repression which then would be in agreement with our data. Given that overexpression of B-MYB was shown to disrupt the DREAM complex leading to activation of gene expression dependent on CHR elements (31), the lack of G 2 /M gene repression in RB-negative cells upon doxorubicin treatment may be caused by an increased B-MYB protein expression (Figure 4C). Interestingly, it was also shown that cells expressing high levels of ectopically expressed B-MYB can enter S phase, even when the p53-p21 pathway is activated (62).…”
Section: Discussionmentioning
confidence: 99%
“…However, microarray analyses of RNA from p130/p107-null mouse embryonal fibroblasts yielded only 37 genes that showed an at least two-fold loss of repression in comparison to wild-type cells upon p53 induction (29). This is especially surprising since loss of p130/p107-binding to DREAM leads to deactivation of the entire complex (30,31). Furthermore, transcriptome analyses identifying p53-DREAM target genes in human cells are not available.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, MMB recruits FOXM1 protein to form MMB-FOXM1 complex, which binds to the promoters of several cell cycle genes and activate their expression in G2/M phase responsible for mitosis (63). A study found that high expression MYBL2 gene disrupts the DREAM complex and increase the MMB complex formation and subsequently triggers the expression of the several target genes driving the cell proliferation in cancer (64). In this way, MMB complex function as opposite of the DREAM complex.…”
Section: Discussionmentioning
confidence: 99%
“…The beads containing phosphorylated proteins were washed once with EBC buffer and analyzed by SDS-PAGE and autoradiography. LIN52 phosphorylation assays were performed as described in [74]. Briefly, extracts from control and DYRK1A-KO U-2 OS cell lines (1 mg/ml) were prepared using EDTAfree EBC buffer supplemented with phosphatase inhibitors, 2 mM DTT, 10 mM MgCl2, 10 mM MnCl2 and 200 ÎŒM ATP, and incubated at 30°C with 6 ng/ÎŒl GST-LIN52.…”
Section: Kinase Assaysmentioning
confidence: 99%